The Effect of Changing Human Gender on Personal Status Issues Between Islamic Jurisprudence and Iraqi Law. - Ahmad Abdulrahman Ahmad; Hemad Majid Ali; Osman Ali Osman (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Gender change is a strange phenomenon that has not been preceded by nations, but has recently appeared in Western societies, as medical progress has clearly contributed to facilitating the process of change, and the electronic and technological development in the means of communication has helped spread this phenomenon among Muslims. Since that time, Muslim scholars have addressed the statement of the position of Islamic Sharia on this process, and this was a matter of dispute between them, as well as legal legislation sought to clarify its legal position on this new issue. And that this paper contributes to honoring the legal stance towards the process of change, by highlighting the evidence of the majority of scholars that come from the Holy Book and the honorable Sunnah and the sound rational and logical evidence that said that the process of change is forbidden. This issue, as well as this paper tried to indicate the legal position of Western and Arab laws of the process of change.